EVALUATION FOR INFLUENCE OF COMBAT VEHICLE'S AGE USAGE TOWARDS MAINTENANCE COST AND AVAILABILITY CONDITION (Case Study in Indonesia Marine Corps, 2005 to 2007) - ARDIANSYAH (NIM. 24006004), HELMI
Combat vehicle is one of the main equipment weapon system for the Indonesia Marines Corps which has special capability in amphibious operation and land operation. The Combat Vehicle availability in performing the operational mission has been influenced by maintenance support system. In the other side, state capability financial to cover requirement of the vehicle combat maintenance budget is very limited. Budget allocation was given to requirement maintenance cost average from 20 to 25 % per annual. Otherwise, maintenance cost tends to increase for each years, eventhough the availability combat vehicle condition decreases. The reason to research the system of Combat Vehicle maintenance is because it is the most dominant Combat Vehicle System for the Indonesia Marines Corps, since maintenance cost value has been required relative bigger to the whole budget logistict support. Meanwhile, Indonesia Marines Corps has applied maintenance system compatible with the guidance book for standard administration of estimating combat vehicle maintenance budget for TNI AL (Indonesia Navy), in which there are assumptions (hypothesis) that combat vehicle of life-cycle usage is 20 years old and it should be disposed or retrofied so its capability and sophistication are not left from the new technology. Since today, there is no research as yet on hypothesis testing which examines and revises the guidence book, but some stakeholders are often to debate with different statements about the usage of combat vehicle's life cicle. As the result, the rising of uncertainty in maintenance system that in the end gives sufferring to the readiness of operational unit. With regard to budget allocation and combat vehicle availability condition, it is necessary for further evaluation to examine that hypothesis so there are the increasing of budget efficiency and effectifity. This research aims to evaluate the influence of combat vehicle maintenance cost and availability condition, in order to increase maintenance efficiency and effectifity during the life-cycles. Statistict method approach is applied for measuring : The first, the interval of distribution for combat vehicle polpulation. The second, bartllete testing to homogeneity for each population. The third, analyses of varians (Anova) to measure the influence of the combat vehicle age for maintenance cost and availability condition. The last, Duncan testing to measure the significant level of the value difference between populations. Next, risk analyses with PID (Probability-Impact Diagram) applied to measure handling option from the risk within population. Then, matrix risk-budget effectiveness analyses applied to map maintenance sistem during the combat vehicle's life cycle. Some data of combat vehicles are confidential level so can not be explicitly displayed but only presented in percent and in the kinds of combat vehicle codes.